Genes affecting the extension of chronological lifespan in Schizosaccharomyces pombe (fission yeast). Issue 4 (3rd November 2020) - Ohtsuka, Hokuto; Shimasaki, Takafumi; Aiba, Hirofumi
Abstract: So far, more than 70 genes involved in the chronological lifespan (CLS) of Schizosaccharomyces pombe (fission yeast) have been reported. In this mini‐review, we arrange and summarize these genes based on the reported genetic interactions between them and the physical interactions between their products. We describe the signal transduction pathways that affect CLS in S . pombe : target of rapamycin complex 1, cAMP‐dependent protein kinase, Sty1, and Pmk1 pathways have important functions in the regulation of CLS extension. Furthermore, the Php transcription complex, Ecl1 family proteins, cyclin Clg1, and the cyclin‐dependent kinase Pef1 are important for the regulation of CLS extension in S . pombe . Most of the known genes involved in CLS extension are related to these pathways and genes. In this review, we focus on the individual genes regulating CLS extension in S . pombe and discuss the interactions among them. Abstract : The microbial chronological lifespan is considered to be a model of cell lifespan after differentiation in higher organisms. In this review, factors extending the lifespan reported thus far in Schizosaccharomyces pombe and the relationships among them were summarized. According to the findings, the TORC1 pathway, PKA pathway, Sty1 pathway, Pmk1 pathway, Ecl1 family genes, Php complex, and cyclin‐dependent kinase Pef1 are considered to contribute to the extension of this yeast's chronological lifespan.